2012
DOI: 10.1095/biolreprod.112.101188
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Aging Hen (Gallus gallus domesticus) as an Animal Model for Uterine Leiomyomas1

Abstract: Uterine leiomyomas, or fibroids, are the most frequent gynecological tumors in premenopausal women with as many as 65% of women becoming clinically symptomatic. Uterine fibroids are benign myometrial tumors that produce large quantities of extracellular matrix proteins. Despite its high morbidity, the molecular basis underlying the development of uterine leiomyomas is not well understood. Domestic hens of Gallus gallus domesticus develop oviductal leiomyomas similar to those found in humans. We investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Leiomyomas of oviduct and it's VL in hens share several histologic and biological features with human uterine leiomyomas [8][9][10] . Our histochemical and immunohistochemical findings confirm that tumours found on the oviduct and it's VL of hens are derived from smooth muscle cells and there are association between tumorigenesis and ovarian sex steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leiomyomas of oviduct and it's VL in hens share several histologic and biological features with human uterine leiomyomas [8][9][10] . Our histochemical and immunohistochemical findings confirm that tumours found on the oviduct and it's VL of hens are derived from smooth muscle cells and there are association between tumorigenesis and ovarian sex steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…administration of oestrogen and progesterone to three weeks old chicks repeated for five weeks was shown to cause leiomyomas of the oviduct VL [1] . Fredrickson et al [8] reported that there were no changes in the plasma concentrations of oestrogen and progesterone in oviduct gland tumours. In addition, such studies on the plasma concentrations of oestrogen and progesterone in leiomyomas of the oviduct VL are limited [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of any data regarding the interval between exposure and fibroids onset in humans, nor are we aware of sufficient data from relevant animal models (Eker rats or domestic hens). 33,34 Given the long half-life of the POPs evaluated, it is likely that the measured concentrations are reasonable approximations of exposure during the relevant period of exposure. Finally, our results would not retain statistical significance after adjusting for multiple comparisons; however, the exploratory nature of our analysis supports the need for additional studies to evaluate associations between POPs and fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is more time-consuming and expensive to produce human therapeutic proteins in industrial bioreactors, the demand for the development of transgenic animals as bioreactors is increasing [ 6 ]. The oviduct of transgenic hens may have advantages over mammalian expression systems as a bioreactor to provide potentially new therapeutic proteins [ 7 ], as laying hens over 2 years of age suffer from fibroid tumors that are similar to human fibroid tumors, thereby making them a good animal disease model [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%